2010
DOI: 10.1093/bja/aep375
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic (H1N1) 2009 influenza

Abstract: The clinical picture in severe cases of pandemic (H1N1) 2009 influenza is markedly different from the disease pattern seen during epidemics of seasonal influenza, in that many of those affected were previously healthy young people. Current predictions estimate that, during a pandemic wave, 12-30% of the population will develop clinical influenza (compared with 5-15% for seasonal influenza) with 4% of those patients requiring hospital admissions and one in five requiring critical care. This review covers the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
98
2
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 47 publications
9
98
2
18
Order By: Relevance
“…According to the results of the study conducted by Viasus et al, H1N1pmd09-positive patients hospitalized during the post-pandemic season were considerably older than those hospitalized during the pandemic season [16]. In our study, patients were more often treated with antiviral therapy in the pandemic season, and with antibiotics and antivirals in the post-pandemic season, which corresponds to the data reported previously [16,17]. Risk factors were more often registered in the pandemic season.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to the results of the study conducted by Viasus et al, H1N1pmd09-positive patients hospitalized during the post-pandemic season were considerably older than those hospitalized during the pandemic season [16]. In our study, patients were more often treated with antiviral therapy in the pandemic season, and with antibiotics and antivirals in the post-pandemic season, which corresponds to the data reported previously [16,17]. Risk factors were more often registered in the pandemic season.…”
Section: Discussionsupporting
confidence: 88%
“…Compared to the pandemic season, during the post-pandemic season, patients were older by an average of seven years, indicating that the patient's age is an important risk factor for the severity of the disease, i.e., grounds for hospitalization during the postpandemic season. According to some European reports and our own study, patients with chronic pulmonary and cardiac diseases, obese people, and pregnant women form the highest-risk group for contracting the pandemic virus [4,17].…”
Section: Discussionmentioning
confidence: 98%
“…The symptoms of H1N1 infection are similar to those of seasonal influenza (high temperature, cough, sore throat, runny nose, headache, and myalgia) 2,7,10,16,17,25 . In a study by Perez-Padilla et al 26 , the most frequently seen symptoms were reported to be fever, cough, and other respiratory problems.…”
Section: African Health Sciencesmentioning
confidence: 96%
“…Moreover, it is extremely complicate to predict the virulence owned by a specific viral strain and its interaction with the host's immune system. On one side, many families of respiratory viruses induce mild or very mild infection so they usually do not constitute a concern for intensive care unit (ICU) physician; on the other side, infection by specific viruses can lead to severe respiratory failure possibly because of an exaggerate inflammatory reaction, which is associated with severe pneumonitis and eventually acute respiratory distress syndrome (ARDS) [5,6]. This condition is usually associated with high mortality despite all treatment efforts, as was the case of pandemic H1N1/09 virus [5].…”
mentioning
confidence: 99%
“…Usually, viruses associated with a high virulence spread as a breakthrough with high mortality rates; eventually, the severity of disease will decrease in the subsequent years. [5][6][7][8].…”
mentioning
confidence: 99%